EVALUATION OF ELECTRIC CONDUCTIVITY AND MILK LACTOSE AS A PRE-INDICATOR OF MASTITIS IN THARPARKAR DAIRY CATTLE (Indian Journal of Animal Production and Management, 2016)
Somatic cell count (SCC) in milk has been shown to be an excellent marker for subclinical mastitis but very  difficult to execute at farm level. Due to the damage to the udder tissue, concentrations of lactose decrease  and concentrations of Na+ and Cl increases in milk which results in increase in electric conductivity. The  present investigation was carried out to investigate the correlation of milk lactose and electric conductivity  with somatic cell count and can be used as an indicator to detect subclinical mastitis (SCM) in Indigenous  zebu Tharparkar cattle. Total 466 milk samples were screened for somatic cell count, 198 samples were  positive for subclinical mastitis. All the samples were analyzed for electrical conductivity (EC) and milk  lactose by deluxe electric conductivity meter manufactured by Systronics India limited, Ahamdabad and  ultrasonic milk analyzer manufactured by Rajasthan Electronics & Instrument Limited (REIL), Jaipur  respectively. The result demonstrated statistically significant (p
Keywords: Electric conductivity; Milk lactose; Somatic cell count; Subclinical mastitis